Optimal control over nonlinear stochastic systems - Trigub, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
The synthesis of optimal control over nonlinear stochastic systems that are described by the Itô equations is reduced to the solution of recurrence relations derived from the Bellman stochastic equation.